Charge-transfer engineering strategies for tailored ionic conductivity at oxide interfaces. Issue 33 (13th August 2020) - Gunkel, F.; Christensen, D. V.; Pryds, N.
Abstract : Based on the example of the p-type LaAlO3 /SrTiO3  interface, we discuss charge-transfer phenomena that tailor the ionic conductivity along oxide heterointerfaces, by providing a confined space-charge layer as channel for oxygen ion conduction. Abstract : Exploiting the electronic charge-transfer across oxide interfaces has emerged as a versatile tool to tailor the electronic and magnetic properties of oxides. Such charge-transfer concepts have been applied to drive insulating oxides into metallic states, to trigger magnetism in non-magnetic oxides, and to render gate-tunable low-dimensional superconductors. While the richness in the electronic and magnetic properties of these systems is the main focus of research, the implications for the ionic transport at oxide interfaces have not received much attention so far. In this communication, we propose that charge-transfer strategies can also be applied to boost ionic charge carrier concentrations at interfaces by orders of magnitude. Based on numerical space-charge modeling, we will illustrate how the 'p-type' charge-transfer predicted between SrO-terminated SrTiO3 and LaAlO3 may foster 2-dimensional oxygen ion conduction at the interface. The ion conduction is effectively separated from impurity dopants, which may allow large concentrations of oxygen vacancies to be achieved in the absence of trapping phenomena. The interface promises high ionic conductivity with nanoscale confinement, potentially allowing the design of field-tunable ionic devices.